Religious Beliefs and Ritual Practices of the Rabha People - Masatoğlu, Mehmet (Fırat Üniversitesi, 2025)
The belief system of the Rabha people, an indigenous community in northeastern India, centers on nature-based beliefs, rituals, and social structures. This study examines the traditional religious and philosophical framework of the Rabha people, emphasizing their profound connection with nature and the central role these beliefs play in their societal life. Rooted in the sanctity of nature and ecological balance, this belief system shapes their way of life, agricultural practices, and social interactions. The Rabha religion is not merely a system of worship but also a symbol of social solidarity and a representation of a harmonious coexistence with nature. Adopting an analytical and critical approach, this study aims to understand the Rabha religious beliefs by exploring their historical and philosophical dimensions. The research delves into the rituals and spiritual practices of the Rabha people, analyzing how these elements influence their cultural identity and strengthen social cohesion. Employing ethnographic observations, oral histories, and a review of written sources, the study sheds light on the continuity and evolution of Rabha cultural and religious traditions. The religious structure of the Rabha community demonstrates a dynamic interaction with diverse cultural and religious influences, preserving and enriching their identity. Their prominent rituals reflect a profound spiritual bond with nature. For instance, offerings to ?ya-Khoksi, the goddess of agriculture, are intended to ensure soil fertility, while prayers to Langa, the deity of rivers, and Hasong, the guardian of forests and wildlife, highlight their reverence for natural elements. These practices underscore the centrality of ecological harmony in Rabha spiritual and practical life. Central to their spiritual life is ancestor worship, which reinforces both individual connections to heritage and collective social harmony. Rituals honoring ancestors not only seek to appease their spirits but also serve as a means of fostering communal unity. The Rabha religion maintains a balance between benevolent deities and malevolent spirits, with practices aimed at ensuring protection from natural calamities or diseases believed to result from malevolent forces. Ritual sacrifices and ceremonies are integral to maintaining this balance, reflecting the community’s emphasis on spiritual equilibrium. This study reveals the Rabha community’s efforts to sustain their cultural identity amidst external influences, underscoring the critical role of oral traditions in transmitting their heritage. By understanding the Rabha religion as a way of life that integrates spiritual practices with ecological mindfulness, the research contributes to a deeper appreciation of their unique cultural and spiritual worldview. Beyond a belief system, the Rabha religion offers a model of sustainable living and a framework for enduring cultural continuity through harmonious interactions with nature. The Rabha people’s religious beliefs and practices are intrinsically linked to their social and ecological context. Their spiritual framework prioritizes environmental stewardship, demonstrating how religious practices can guide sustainable interactions with natural resources. This approach not only fosters community resilience but also strengthens their cultural foundations in the face of external changes. The Rabha religion’s integration of ecological consciousness with spiritual devotion illustrates a holistic model for cultural sustainability, where traditional practices adapt to changing circumstances while preserving core values. Through this exploration, the study highlights the Rabha religion’s multifaceted role as a spiritual, social, and ecological system. It provides valuable insights into how indigenous belief systems can contribute to broader discussions on sustainability and cultural resilience. The Rabha religion’s emphasis on balance—between nature and humanity, tradition and change—offers a compelling perspective for understanding the enduring interplay between spirituality and ecology in sustaining community identity.

Rabha Halkının inanç sistemi, Hindistan’ın kuzeydoğu bölgelerinde yaşayan Rabha kabilesinin doğa temelli inançları, ritüelleri ve toplumsal yapısına odaklanır. Çalışma, Rabha halkının geleneksel dini ve felsefi yapısını, doğayla olan derin bağları ve bu bağların toplumsal hayatlarındaki merkezi rolü üzerinden inceler. Doğanın kutsallığına ve ekolojik dengeye dayanan bu inanç sistemi, topluluğun yaşam tarzını, tarımsal uygulamalarını ve sosyal ilişkilerini biçimlendirir. Rabha dini, sadece bir inanç sistemi değil, aynı zamanda toplumsal dayanışmanın bir sembolü ve doğayla uyum içinde sürekli bir varoluşun temsili olarak değerlendirilir. Bu çalışma, Rabha dini inancını anlamak için analitik ve eleştirel bir yaklaşım benimsemiş, hem tarihsel hem de felsefi boyutlarıyla topluluğun inanç sistemini incelemeyi amaçlamıştır. Araştırmada, Rabha halkının ritüelleri ve manevi pratikleri detaylı bir şekilde ele alınmış, bunların kültürel kimliklerini ve toplumsal dayanışmalarını nasıl şekillendirdiği çözümlemeye çalışılmıştır. Araştırma, alanyazında mevcut olan etnografik verilerin analiz edilmesi, sözlü tarih çalışmalarının incelenmesi ve yazılı kaynakların değerlendirilmesi yoluyla geliştirilmiştir. Böylece, Rabha toplumunun dini ve kültürel devamlılığını nasıl sürdürdüğü açığa çıkarılmıştır. Rabha topluluğunun dini yapısı, çeşitli kültürel ve dini etkilerle esnek bir şekilde etkileşim kurarak kendi kimliğini korumuş ve zenginleşmiştir. Topluluğun özellikle öne çıkan ritüelleri, doğayla derin bir manevi bağı yansıtır. Doğanın kutsallığına inanç, tarımsal faaliyetlere odaklanan ritüellerde açıkça görülmektedir. Örneğin, Rabhalar, tarım tanrıçası ?ya-Khoksi’ye adaklar sunarak toprağın verimliliğini sağlama amacı gütmektedir. Benzer şekilde, nehirler ve su kaynakları için Langa’ya dua edilirken, ormanların ve yabani yaşamın koruyucusu olarak Hasong’ı kutsal kabul ederler. Rabhalar, manevi dünya ile maddi dünyanın arasındaki dengenin korunmasına büyük önem atfetmektedir. Atalara tapınma, bu topluluğun dini ve kültürel yapısında merkezi bir rol oynamaktadır. Atalara sunulan adaklar ve yapılan ritüeller, hem bireylerin kökleriyle olan bağlarının güçlenmesine hem de toplumsal dayanışmanın pekişmesine olanak tanır. Ataların ruhlarını memnun etmeye yönelik törenler, Rabhalar için sadece bir dini uygulama değil, aynı zamanda bir sosyal uyum arayışını ifade eder. Rabha dini, iyi ve kötü tanrılar arasında bir denge üzerine kuruludur. Bu çerçevede, olumlu değerleri temsil eden iyi tanrılara dua edilerek refah ve mutluluk arayışı sürerken, kötü ruhlara karşı da belirli ayinler düzenlenerek topluluğun güvende kalması hedeflenir. Örneğin, doğal afetler ya da hastalıkların kötü ruhların etkisi olduğuna inanılan durumlarda, hayvan kurbanları veya ritüel uygulamaları bu etkilerin azaltılması amacıyla kullanılır. Bu dini pratikler, Rabha toplumu için manevi dengenin korunmasında kritik bir rol oynar. Bu araştırmanın temel amacı, Rabha halkının kültürel kimliğini koruma yöntemlerini ortaya koymak ve bu kimliğin dışsal dinamiklere rağmen nasıl direnç gösterdiğini anlamaktır. Rabhaların dini pratikleri, sözlü gelenekler aracılığıyla nesilden nesile aktarılmış, toplumsal ve kültürel bir hafıza oluşturmuştur. Rabha dini üzerine yapılan bu inceleme, topluluğun inanca dayalı kimliğini, toplumsal yaşamını ve doğa ile olan ilişkisini anlamamıza katkı sağlamaktadır. Bu bağlamda, Rabha dini, bir ibadet sistemi olmanın ötesinde, bireylerin toplumsal rolleri ve doğayla uyumlu bir yaşam tarzı sunarak topluluğun sürekliliğini sağlamaktadır. Rabhalar, dinlerini sadece bir ibadet sistemi olarak değil, aynı zamanda yaşam tarzı ve doğayla uyumlu bir varoluş çerçevesi olarak benimsemiştir.
Rabha Halkının İnanç Dünyası ve Ritüel Pratikleri
Keywords: History of Religion; Dinler Tarihi; Studies in Eastern Religious Traditions; Doğu Dinleri ve Gelenekleri Araştırmaları